Citizen Kane. - Mankiewicz, Herman J. (Herman Jacob), 1897-1953; Welles, Orson, 1915-1985 (Universal Pictures, 2003)
A newspaper tycoon dies, and a magazine reporter interviews his friends in an effort to discover the meaning of his last words.